Functional Glyco-Nanogels for Multivalent Interaction with Lectins - Tang, Jo Sing Julia (Molecules, 2019)
Interactions between glycans and proteins have tremendous impact in biomolecular interactions. They are important for cell–cell interactions, proliferation and much more. Here, we emphasize the glycan-mediated interactions between pathogens and host cells. Pseudomonas aeruginosa, responsible for a huge number of nosocomial infections, is especially the focus when it comes to glycan-derivatives as pathoblockers. We present a microwave assisted protecting group free synthesis of glycomonomers based on lactose, melibiose and fucose. The monomers were polymerized in a precipitation polymerization in the presence of NiPAm to form crosslinked glyco-nanogels. The influence of reaction parameters like crosslinker type or stabilizer amount was investigated. The gels were characterized in lectin binding studies using model lectins and showed size and composition-dependent inhibition of lectin binding. Due to multivalent presentation of glycans in the gel, the inhibition was clearly stronger than with unmodified saccharides, which was compared after determination of the glycan loading. First studies with Pseudomonas aeruginosa revealed a surprising influence on the secretion of virulence factors. Functional glycogels may be in the future potent alternatives or adjuvants for antibiotic treatment of infections based on glycan interactions between host and pathogen.